An evaluation of feto-maternal outcome in oligohydramnios: a prospective study - Chaudhary, Isha; Mittal, Rita; Chauhan, Subhash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Oligohydramnios is defined as amniotic fluid index (AFI) below 5th centile for the gestational age. AFI is an index of foetal well-being. It is associated with increased pregnancy complications, perinatal morbidity and mortality. AFI assessment would help to identify women who need increased antepartum and intra-partum surveillance. It occurs in 1-5% of pregnancies at term. We intended to do a specific study at our centre IGMC, Shimla to compare the maternal and perinatal outcome in pregnant women having isolated oligohydramnios at term with those having normal AFI. Methods: This was a prospective observational case control comparative study conducted in the department of Obstetrics and Gynecology at Indira Gandhi Medical College, Shimla between 1st July 2019 to 30th June 2020. 50 cases with AFI≤5cm and 50 controls with AFI 8-20cm at 37-42 weeks were enrolled. Maternal and neonatal outcomes were compared. Results: There was more foetal growth retardation (FGR) in study group 28% as compared to 10% in control group, more induction of labour in study group 50% as compared to control group 38%. 46% of patients from study group while only 20% patients from control group underwent LSCS. Significant difference observed between 1- and 5-minute APGAR scores in both groups. Low birth weight <2.5 kg was seen in 24% of neonates from study group and 10% of neonates from the control group. 50% of neonates from the study group were admitted in NICU for complications. Conclusions: AFI is a valuable screening test for predicting foetal distress in labour requiring caesarean section. Timely intervention is required to reduce perinatal morbidity and mortality.